2006
DOI: 10.1080/14034940600551640
|View full text |Cite
|
Sign up to set email alerts
|

Diverging trends in the incidence and mortality of stroke during the period 1986—2002: A study from the Stroke register in Kaunas, Lithuania

Abstract: Findings from our study indicating no positive changes in the incidence of stroke but instead an increase among middle-aged women in Kaunas are disturbing. These results suggest a need for the intensification of appropriate strategies for stroke prevention by the public health officials in Lithuania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…14,34 The case-fatality trends were declining in most studies, during the last decades, but in a minority they were stable. 33 More recent studies of case-fatality at 28 or 30 days have also shown declining 14,15 or stable 10 trends. In the Framingham study the incidence of stroke has decreased during the last 50 years for men and women, but the 30-day case-fatality decreased significantly only among men.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…14,34 The case-fatality trends were declining in most studies, during the last decades, but in a minority they were stable. 33 More recent studies of case-fatality at 28 or 30 days have also shown declining 14,15 or stable 10 trends. In the Framingham study the incidence of stroke has decreased during the last 50 years for men and women, but the 30-day case-fatality decreased significantly only among men.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…The temporal trends of stroke epidemiology have been studied in Sweden [1][2][3][4] and other countries during the last decades, [5][6][7][8][9][10][11][12][13][14][15][16][17] but although stroke mortality has decreased for many decades, stroke incidence trends have been more divergent. As the elderly population is growing in the developed countries and stroke incidence is much higher among the elderly, time trends for stroke incidence are important in planning of health strategies and to evaluate primary and secondary preventive measures.…”
mentioning
confidence: 99%
“…Centers within different countries were selected based on previous experience in running population-based or hospital-based stroke registers. In Kaunas, Lithuania, 13 Dijon, France, 7 London, UK, 11 and Warsaw, Poland, 14 well-established population-based stroke registers have been running since 1986,1982,1995, and 1991, respectively. In Menorca, Spain, and Sesto Fiorentino, Italy, hospitalbased stroke registers were initiated for 2 previous European Union Biomedicine and Health Programme (BIOMED) II Projects starting from 1993 15,16 and for this study, population-based registers were established in both centers.…”
mentioning
confidence: 99%
“…The stroke events were associated with high blood pressure and diabetes in Pacific women [10]. In Lithuania case fatality significantly decreased both among men and women and incidence of stroke significantly increased among women during 1986-2002 [11]. Declining case fatality can result from better medical management or a change in the severity of stroke.…”
Section: Discussionmentioning
confidence: 99%